To the knowledge of the genera Asactopholis Brenske, 1894, Dasylepida Moser, 1913 and Lepidiota Kirby, 1826 in Indochina (Coleoptera: Scarabaeidae: Melolonthinae: Leucopholini) - A.M. Prokofiev (Кавказский энтомологический бюллетень, 2015)
The genera Asactopholis, Dasylepida and Lepidiota of the Indochinese fauna (without Peninsula of Malacca) are discussed. Nine new species and subspecies are described: A. bicolor nigrimargo subsp. n., A.  dalatensis sp.  n., D.  rudepunctata aciculata subsp.  n., L.  acuminatops sp.  n., L.  adelphopyga sp.  n., L. irokezica sp. n., L. medvedevi sp. n., L. nho sp. n. and L.  omnipodex sp.  n. The following new synonyms are established: Asactopholis Brenske, 1894 = Empectida Moser, 1913,  syn.  n.; Dasylepida nana (Sharp, 1876)  = D.  fissa Moser, 1913,  syn.  n.; Lepidiota discedens Sharp, 1876 = L.  hispida Frey, 1969,  syn.  n. The keys for identification of the species of the genera Dasylepida and Lepidiota of the fauna of China and Indochina (without Peninsula of Malacca) are given. Diagnoses of the new taxa: A.  bicolor  nigrimargo  subsp.  n. from North Thailand differs from the nominotypical subspecies in the smaller size, black-margined sides of the elytra and denser puncturation of the dorsal surface and abdomen. Asactopholis dalatensis  sp.  n. is most similar to A. capucinus (Fairmaire, 1893) and A. bicuspis Frey 1970 but differs from these species in the smaller size, less dense scale cover, broader tooth of the claws, shape of the pygidium and the aedeagus. Dasylepida rudepunctata aciculata subsp.  n. from Dalat Mt. differs from the nominotypical subspecies in the smaller size and narrower scales on the apices of the elytra, pygidium and propygidium in the males and apparently in the well-developed pronotal sulcus in the females. Lepidiota acuminatops sp.  n. is hardly distinguishable externally from L. acuminata Moser, 1913 but is distinctive in the shape of the aedeagus. Lepidiota irokezica sp. n. is similar to L. discendens Sharp, 1876 but differs from the latter in the presence of the specialized setae along midline of the pronotum only. Lepidiota omnipodex sp. n. is unique in the structure of the pygidium in both sexes and in the shape of the aedeagus. Lepidiota adelphopyga sp. n. is very similar to the previous species but differs in the smaller number of the bristles at the apices of the hind tibiae in both sexes and in the shape of the male’s genitalia and the female’s pygidium. Lepidiota nho sp. n. differs from all the other Lepidiota spp. in the small size and in the shape of the aedeagus.